Trends in anti-UV films or composites: A bibliometric study - Dieter Rahmadiawan; Thiago F. Santos; Navid Aslfattahi; Shih-Chen Shi; Eko Indrawan; Athaya Ramadhan; Zainal Abadi (Universitas Negeri Padang, 2025)
Anti-UV films and composites play a critical role in protecting materials from ultraviolet-induced degradation, which can weaken polymers, reduce product lifespan, and compromise performance in sectors such as food packaging, outdoor coatings, and biomedical devices. The growing emphasis on sustainability and the need for environmentally friendly protective materials have further accelerated research on UV-shielding technologies that incorporate biopolymers, multifunctional additives, and renewable resources. This study presents a comprehensive bibliometric analysis of global research on anti-UV films and composites over the period 2014–2024. Data were retrieved from the Scopus database and analyzed using Bibliometrix (R package) and VOSviewer were employed to analyze publication patterns, map keyword networks, and visualize thematic evolution, as these tools enable robust quantitative and structural mapping of large bibliographic datasets. Three dominant thematic clusters were identified: (i) nanoparticle-based UV shielding using inorganic fillers such as ZnO and TiO₂, (ii) multifunctional films integrating UV protection with antibacterial and antioxidant properties, and (iii) biopolymer-based matrices emphasizing mechanical durability and environmental sustainability. These clusters highlight the convergence of performance, sustainability, and multifunctionality as key drivers shaping current research directions. Despite significant progress, the analysis reveals limited attention to scalability, industrial compatibility, and long-term performance evaluation. The findings underscore the need for future research to incorporate pilot-scale processing, life-cycle assessments, and interdisciplinary collaboration to bridge the gap between laboratory formulations and commercial implementation. Overall, this bibliometric study provides a consolidated understanding of the evolution and research landscape of anti-UV films and composites.